P80 Extrapolating lung clearance index (LCI) from shortened measurements. (12th November 2015) - Tanou, K; Irving, S; Ahmad, F; Fleming, L; Rosenthal, M; Bush, A
Abstract : Introduction and objectives: Shortened multiple breath washouts (MBW) are attractive in young children, where a long test time may not be tolerable (Thorax 2013;68:586–7). Lung clearance index (LCI) is usually calculated at 1/40 th of the starting concentration (LCIstd ), but in shorter MBWs the LCI is calculated at 1/20 th of the starting concentration (LCI0.5 ). LCI0.5 and LCIstd are closely correlated but not interchangeable, and so we calculated an extrapolated full LCI (LCIex ) from LCI0.5 . Our hypothesis was that extrapolated LCI (LCIex ) will better reflect LCIstd than LCI0.5 and be more sensitive to intervention. Methods: Condition-specific equations for cystic fibrosis (CF), primary ciliary dyskinesia (PCD) and asthma, and an overall equation for all 3 groups, were developed to convert LCI0.5 to LCIex from data previously analysed (n = 90, Thorax 2014;69[Suppl 2 ]A166). LCIstd, LCI0.5 and LCIex were then calculated for new cohorts (n = 70, 20 asthma, 30 CF, 20 PCD), and LCIex was compared to LCIstd . CF patients receiving IV antibiotics (n = 17) and asthma patients receiving triamcinolone (n = 32)) also had LCIstd, LCI0.5 and LCIex calculated and compared. The upper limit of normal for LCIstd was calculated from healthy controls. LCIex was compared to LCIstd with a Bland-Altman plot. Results: In CF, at higher LCIs, the spread between LCIex and LCIstd grew but there was no bias. For PCD and asthma agreement remained very good. There was no significant difference between LCIstd and LCIex . Results for positive and negative prediction of LCIstd for LCI0.5 and LCIex are shown in the Table 1 . LCIex and LCI0.5 were also sensitive to interventions in asthmatic and CF patients, although in general LCIstd had better p values. Conclusions: LCIex performed better than LCI0.5 in predicting results of LCIstd . However, LCIex did not always reflect LCIstd, particularly in CF, so the two cannot be used interchangeably in lung disease.